What determines the citation frequency of ecological papers? - Leimu, R; Koricheva, J (2005)
Citation frequencies of scientific articles are increasingly used for academic evaluation in various disciplines, including ecology. However, the factors affecting citation rates have not been extensively studied. Here, we examine the association between the citation frequency of ecological articles and various characteristics of journals, articles and authors. Our analysis shows that the annual citation rates of ecological papers are affected by the direction of the study outcome with respect to the hypothesis tested (supportive versus unsupportive evidence), by article length, by the number of authors, and by their country and university of affiliation. These results cast doubt on the validity of using citation counts as an objective and unbiased tool for academic evaluation in ecology.